Ornamental Palm Species of Palu City, Central Sulawesi, Indonesia - Amila Farwizah Tiwatu; Ramadanil Ramadanil; Zahwa Arzeti Bilbina; Regita Cahyani; Muhammad Ardian Satrio Nugraha; Amar Amar; Muhd Nur Sangadji (Universitas Sam Ratulangi, 2024)
A research-entitled ornamental palm species of Palu city, central Sulawesi, Indonesia has been conducted from May to September 2024. The goal of the study was to document ornamental palm in Palu City. The direct observation through botanical exploration method was performed to inventory ornamental plant in 8 districts of Palu. All ornamental palms samples were collected and photographed then identified at the Laboratory of Plant Biosystematics, Department of Biology, Faculty of Mathematics and Natural Sciences and the Herbarium Celebense (CEB), Tadulako University Palu. Additional data included local name, botanical name, family, plant habitus (life form), were noted. Specimens with their label were deposited at CEB, Tadulako University Palu, Indonesia. There were 16 (sixteen) ornamental palms namely: Areca cathechu, Cocos nucifera, Phoenix dactilyfera, Elaeis guineensis, Cyrtostachys renda, Corypha utan, Roystonia regia, Saribus rotundifolius, Wodyetia bifurcata, Adonidia merrilii, Hyophorbe lagenicaulis, Chrysalidocarpus decaryi, Bismarckia nobilis, Chamaedorea elegans, Licuala grandis, and Rhapis excelsa